Representasi Elemen Budaya Cina Kontemporer dalam Perancangan Ornamen Food Court Pondok Indah Mall 2 - Natissa Kansha Kanani; Adisti Ananda Yusuff (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Cultural approaches in interior design can build spatial identity while reflecting cultural values. Food courts illustrate how dining spaces evolve into communal environments that support social interaction and cultural expression. This study examines the representation of contemporary Chinese cultural elements in the ornament design of the Pondok Indah Mall 2 food court in Jakarta. Using a research-through-design method, traditional elements such as lanterns, calligraphy scrolls, and symbolic motifs are reinterpreted into contemporary interior features. The main design intervention transforms structural pillars into large-scale ornaments inspired by Chinese scrolls and modular lantern installations that function as lighting and spatial markers. Traditional symbolism is translated into simplified geometric forms and modern materials to meet functional and aesthetic needs. The resulting design demonstrates how cultural heritage can be adaptively transformed into contemporary interior spaces, strengthening spatial identity and enhancing cultural appreciation within urban public environments.